Sexuality and School. Possible Programmatics perspectives - Wainerman, Catalina; Chami, Natalia (Education Policy Analysis Archives, 2014)
The Argentinean National Law 26.150 (2006) requires from schools -both public and private- to carry out an Integral Program of Sexual Education. Already before the law had been passed, some schools had conducted diverse programs on sexual education. In order to take advantage of these experiences for the design of further actions within the Educational System, a research was conducted in four jurisdictions, the main objective of which was to learn about the programmatic perspectives and pedagogical strategies employed. This was accomplished by means of interviewing 72 actors in 24 schools. This article summarizes some of the main results achieved.